2011
DOI: 10.1074/jbc.m111.244053
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Serine/Threonine Protein Phosphatase 5 (PP5:PPP5c) in Mice Reveals a Novel Role for PP5 in the Regulation of Ultraviolet Light-induced Phosphorylation of Serine/Threonine Protein Kinase Chk1 (CHEK1)

Abstract: Background:The roles of PP5 in normal biology are poorly understood. Results: To help evaluate the biological actions of PP5, a Cre/loxP-conditional mouse line was generated. Conclusion: In response to UV light, PP5 regulates the phosphorylation of Chk1 at Ser-345. Significance: Understanding the biological roles for phosphatases is critical for understanding the role of reversible phosphorylation in the control of signaling networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Our studies on the Ppp5 D274 A 'knockin' (KI) (Ppp5KI) mouse are the first to report the effects of inactivated Ppp5 on GR phosphorylation and differentiation in adipose tissue of an animal model. Homozygous Ppp5KI and PP5KO mice were viable and fertile, but selection against the homozygous male offspring of Ppp5KI heterozygous intercrosses was statistically significant and a similar prenatal effect was observed in one of the KO models [18]. Our genetic analyses further show that there is a trend towards significance for selection against homozygous Ppp5KI female offspring and 13.5-day male/female embryos of Ppp5 D274 A/ + intercrosses.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Our studies on the Ppp5 D274 A 'knockin' (KI) (Ppp5KI) mouse are the first to report the effects of inactivated Ppp5 on GR phosphorylation and differentiation in adipose tissue of an animal model. Homozygous Ppp5KI and PP5KO mice were viable and fertile, but selection against the homozygous male offspring of Ppp5KI heterozygous intercrosses was statistically significant and a similar prenatal effect was observed in one of the KO models [18]. Our genetic analyses further show that there is a trend towards significance for selection against homozygous Ppp5KI female offspring and 13.5-day male/female embryos of Ppp5 D274 A/ + intercrosses.…”
Section: Discussionsupporting
confidence: 50%
“…We demonstrate that preadipocytes expressing inactivated Ppp5 differentiate more slowly in culture than in wild-type preadipocytes and that more stromal cells, which include preadipocytes, are present in the gonadal fat pads of Ppp5 D274A/D274A mice, data which support a block in an early step of preadipocyte differentiation. Two mouse PP5KO models were previously analysed without noting decreased amounts of adipose tissue or biochemical alterations in this tissue [17,18]. Our studies on the Ppp5 D274 A 'knockin' (KI) (Ppp5KI) mouse are the first to report the effects of inactivated Ppp5 on GR phosphorylation and differentiation in adipose tissue of an animal model.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been reported that the overexpression of PPP5C has been observed in several solid cancer types (42)(43)(44). In addition, overexpression of PPP5C has been demonstrated to promote cell proliferation and tumor progression (35).…”
Section: Discussionmentioning
confidence: 99%